Tuned with a Tune: Talker Normalization via General Auditory Processes - Laing, Erika J.; Liu, Ran; Lotto, Andrew J.; Holt, Lori L. (Frontiers in Psychology, 2012)
Voices have unique acoustic signatures, contributing to the acoustic variability listeners must contend with in perceiving speech, and it has long been proposed that listeners normalize speech perception to information extracted from a talker’s speech. Initial attempts to explain talker normalization relied on extraction of articulatory referents, but recent studies of context-dependent auditory perception suggest that general auditory referents such as the long-term average spectrum (LTAS) of a talker’s speech similarly affect speech perception. The present study aimed to differentiate the contributions of articulatory/linguistic versus auditory referents for context-driven talker normalization effects and, more specifically, to identify the specific constraints under which such contexts impact speech perception. Synthesized sentences manipulated to sound like different talkers influenced categorization of a subsequent speech target only when differences in the sentences’ LTAS were in the frequency range of the acoustic cues relevant for the target phonemic contrast. This effect was true both for speech targets preceded by spoken sentence contexts and for targets preceded by nonspeech tone sequences that were LTAS-matched to the spoken sentence contexts. Specific LTAS characteristics, rather than perceived talker, predicted the results suggesting that general auditory mechanisms play an important role in effects considered to be instances of perceptual talker normalization.